Impact of naturally leaking carbon dioxide on soil properties and ecosystems in the Qinghai-Tibet plateau - Xiaohong Zhao (Nature Portfolio, 2017)
Abstract One of the major concerns for CO2 capture and storage (CCS) is the potential risk of CO2 leakage from storage reservoirs on the shallow soil property and vegetation. This study utilizes a naturally occurring CO2 leaking site in the Qinghai-Tibet Plateau to analog a “leaking CCS site”. Our observations from this site indicates that long-term CO2 invasion in the vadose zone results in variations of soil properties, such as pH fluctuation, slight drop of total organic carbon, reduction of nitrogen and phosphorus, and concentration changes of soluble ions. Simultaneously, XRD patterns of the soil suggest that crystallization of soil is enhanced and mineral contents of calcite and anorthite in soil are increased substantially. Parts of the whole ecosystem such as natural wild plants, soil dwelling animals and microorganisms in shallow soil are affected as well. Under a moderate CO2 concentration (less than 110000 ppm), wild plant growth and development are improved, while an intensive CO2 flux over 112000 ppm causes adverse effects on the plant growth, physiological and biochemical system of plants, and crop quality of wheat. Results of this study provide valuable insight for understanding the possible environmental impacts associated with potential CO2 leakage into shallow sediments at carbon sequestration sites.